2007
DOI: 10.1111/j.1365-2303.2007.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Referral compliance, outcome and predictors of CIN after repeated borderline cervical smears in the Netherlands

Abstract: This finding may be used for prioritizing women for colposcopy on the basis of their age. More stringent use of the diagnosis of BNC, higher thresholds for colposcopically directed biopsy and introduction of HPV triage, combined with more specific new techniques or combination of techniques such as molecular markers for P16, MIB-1 and L1 may reduce the unnecessary high referral rate and over treatment of healthy women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…A complete evaluation of the cervical transformation zone was required for negative diagnosis. Conventional Pap smear specimens were immunostained for CA-IX as described previously [5,7,11,12]. The presence of any of 13 high-risk HPV (H-HPV) DNA types (16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, or 68) was detected using HC2 (Digene Corp., Gaithersburg, MD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete evaluation of the cervical transformation zone was required for negative diagnosis. Conventional Pap smear specimens were immunostained for CA-IX as described previously [5,7,11,12]. The presence of any of 13 high-risk HPV (H-HPV) DNA types (16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, or 68) was detected using HC2 (Digene Corp., Gaithersburg, MD).…”
Section: Methodsmentioning
confidence: 99%
“…It is not clear, however, how to identify them. After a diagnosis of AGC-NOS, additional screening is needed to distinguish between those women who have a SCL from those who do not in order to avoid an unnecessarily high referral rate and over-treatment of healthy women [7]. Our Gynecologic Oncology Group study, GOG-0171, found that additional screening for high-risk HPV (H-HPV) infection by Hybrid Capture II (HC2) among women with AGC-NOS in the U.S. produced an estimated 97% sensitivity, 87% specificity, 99% negative predictive value (NPV), and a positive predictive value (PPV) of only 77%, when treating histological diagnosis as the truth.…”
Section: Purposementioning
confidence: 99%